Neural crest lineage analysis: from past to future trajectory - Tang, Weiyi (Development, 2020)
Since its discovery 150 years ago, the neural crest has intrigued investigators owing to its remarkable developmental potential and extensive migratory ability. Cell lineage analysis has been an essential tool for exploring neural crest cell fate and migration routes. By marking progenitor cells, one can observe their subsequent locations and the cell types into which they differentiate. Here, we review major discoveries in neural crest lineage tracing from a historical perspective. We discuss how advancing technologies have refined lineage-tracing studies, and how clonal analysis can be applied to questions regarding multipotency. We also highlight how effective progenitor cell tracing, when combined with recently developed molecular and imaging tools, such as single-cell transcriptomics, single-molecule fluorescence in situ hybridization and high-resolution imaging, can extend the scope of neural crest lineage studies beyond development to regeneration and cancer initiation.